Plan de marketing que permita la recuperación de cartera de clientes en la empresa catálogo SRH, en la ciudad de Guayaquil - Ramos Guayllas, Génesis Yulissa (2018)
The title work "Marketing plan that allows the recovery of customer portfolio in the company SRH Catalog, in the city of Guayaquil", among the objectives are: Identify the clients that manage the sub-distributors of the company SRH, in the market of sale ofclothes by catalog. Investigate if strategies have been implemented for the recovery of clients, what strategies are appropriate and Design a marketing plan that allows thefulfillment of the proposed objectives. The work was justified from the theoretical pointof view, considering the consultation of several authors of expert texts in the subjectrelated to marketing, sales and recovery of client portfolio. In the methodological part, quantitative research was used, with the technique of the survey, by means of theinstrument of the questionnaire, elaborated based on the variables. The survey was applied in a personal way to the target group identified as sub-distributors of the productsof the SRH company……